Adult Learners' Perspectives on Their Engagement in a Hybrid Learning Postgraduate Programme. Issue 2 (4th May 2018) - Johnson, Ensa; Morwane, Refilwe; Dada, Shakila; Pretorius, Gaby; Lotriet, Marena
Abstract: Student engagement is a prerequisite for successful learning. Due to the tremendous change in the use of information and communication technologies, the nature of this engagement has had to adapt to fit a hybrid approach of teaching and learning. In this qualitative study, three focus group discussions were conducted that aimed to investigate adult learners' perspectives on their engagement in a hybrid learning postgraduate programme. Deductive content analysis was done of the transcribed data using Pittaway's Engagement Framework. Main findings were that adult learners' computer literacy skills impacted on their own self-efficacy towards their ability to study and use technology. Lecturers' social engagement, especially their support to students, was also highlighted. Other factors, such as Internet access and power failures, hampered adult learners' access to online activities. An adapted engagement framework for adult learners is proposed and should be taken into account when developing new online programmes for adult learners.